Health promotion in Australian multi-disciplinary primary health care services: Case studies from South Australia and the Northern Territory - Baum, F.; Freeman, T.; Jolley, G.; Lawless, A.; Bentley, M.; Värttö, K.; Boffa, John; Labonte, R.; Sanders, D. (2014)
© The Author (2013). Published by Oxford University Press. All rights reserved. This paper reports on the health promotion and disease prevention conducted at Australian multi-disciplinary primary health care (PHC) services and considers the ways in which the organizational environment affects the extent and type of health promotion and disease prevention activity. The study involves five PHC services in Adelaide and one in Alice Springs. Four are managed by a state health department and two by boards of governance. The study is based on an audit of activities and on 68 interviews conducted with staff. All the sites undertake health promotion and recognize its importance but all report that this activity is under constant pressure resulting from the need to provide services to people who have health problems. We also found an increased focus on chronic disease management and prevention which prioritized individuals and behavioural change strategies rather than addressing social determinants affecting whole communities. There was little health promotion work that reflected a salutogenic approach to the creation of health. Most activity falls under three types: parenting and child development, chronic disease prevention and mental health. Only the non-government organizations reported advocacy on broader policy issues. Health reform and consequent reorganizations were seen to reduce the ability of some services to undertake health promotion. The paper concludes that PHC in Australia plays an important role in disease prevention, but that there is considerable scope to increase the amount of community-based health promotion which focuses on a salutogenic view of health and which engages in community partnerships.